A comparative study between actual possession time and match results for Peshmerga and Nawroz clubs in the Iraqi Under-21 Reserve League of football - Qader, Asst. Prof. Dr. Yassin Abdul-Munaf (Sulaimani Journal for Humanities, 2026)
This study aimed to identify the actual possession time of Peshmerga and Nawroz clubs in the Iraqi Under-21 Reserve League and to compare them across six 15-minute quarters. The study also sought to identify differences between Peshmerga and Nawroz within each quarter and in the overall possession time. This was then correlated with match results. The researcher used a descriptive comparative approach, and the study sample included six matches from both teams across two different seasons, totaling 24 matches in the 2023-2024 and 2024-2025 seasons. Technical analysis tools were used to collect and statistically process the data using the t-test and Pearson's correlation coefficient. The study reached several conclusions, including a fundamental difference in the nature of the relationship between the two clubs. Peshmerga suffers from an inverse correlation (the more possession, the worse the result), while Nowruz enjoys a direct correlation (the more possession, the better the result). The increased strength of the inverse correlation for Peshmerga in the second season indicates the team's reliance on ball circulation without offensive effectiveness, making prolonged possession a tactical burden leading to negative results. The researcher recommends that the coaching staff focus on purposeful possession drills in attacking areas, rather than simply circulating the ball in defensive areas. Since the relationship between increased possession time and results was inverse, the researcher recommends adopting fast-paced attacking strategies in certain situations to ensure reaching the goal with the fewest possible passes and the highest possible efficiency. The researcher also recommends training the team on how to deal with sudden ball losses, as teams that maintain possession for extended periods are vulnerable to counter-attacks. The concepts of counter-pressing should be reinforced to regain possession immediately and prevent the opponent from exploiting possession gaps.
Keywords: Actual possession time; match results; comparative study; reserve league; under 21